2020
DOI: 10.1002/jha2.114
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of pain trajectories among patients with sickle cell disease hospitalized for vaso‐occlusive crisis: A data‐driven approach

Abstract: Background Vaso‐occlusive crises (VOCs) are the hallmark of sickle cell disease (SCD), with higher severity among hospitalized patients. Clustering hospitalizations with similar pain trajectories could identify vulnerable patient subgroups. Aims were to (a) identify clusters of hospitalizations based on pain trajectories; (b) identify factors associated with these clusters; and (c) determine the association between these clusters and 30‐day readmissions. Methods We retrospectively included 350 VOC hospitalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…By characterizing short‐term pain trajectories in children with CP, future studies may focus on identifying factors that have an impact on or improve pain trajectories. Studies of pain trajectories in other paediatric chronic conditions, such as rheumatoid arthritis and sickle cell anaemia, reported similar results 33,34 . Children with juvenile rheumatoid arthritis also grouped into concerning pain trajectories, with chronically moderate and increasing or decreasing pain trajectories; however, these were measured every 6 months for 5 years 33 .…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…By characterizing short‐term pain trajectories in children with CP, future studies may focus on identifying factors that have an impact on or improve pain trajectories. Studies of pain trajectories in other paediatric chronic conditions, such as rheumatoid arthritis and sickle cell anaemia, reported similar results 33,34 . Children with juvenile rheumatoid arthritis also grouped into concerning pain trajectories, with chronically moderate and increasing or decreasing pain trajectories; however, these were measured every 6 months for 5 years 33 .…”
Section: Discussionmentioning
confidence: 89%
“…Studies of pain trajectories in other paediatric chronic conditions, such as rheumatoid arthritis and sickle cell anaemia, reported similar results. 33 , 34 Children with juvenile rheumatoid arthritis also grouped into concerning pain trajectories, with chronically moderate and increasing or decreasing pain trajectories; however, these were measured every 6 months for 5 years. 33 Children hospitalized for sickle cell vaso‐occlusive crises experienced slow, moderate, and rapidly decreasing pain trajectories over 1 week.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are consistent with a previous report examining acute pain trajectories in SCD, which indicated that hospitalizations among female patients or among those with more frequent complications of SCD were associated with a slower decline in pain intensity. 25 However, in retrospective studies, including this study, acute pain trajectories were examined after presentation to the ED, and the effect of duration of pain experienced at home prior to presentation to the ED on observed pain trajectories in an acute care setting could not be assessed. In addition, although we could not definitely assess for history of chronic pain in this retrospective study, it is likely that some individuals with high HCU also had chronic pain, and the impact of history of chronic pain on pain trajectories could not be assessed.…”
Section: Discussionmentioning
confidence: 99%